Association between Physical Activity Level and Body Weight Status, Body Composition, Cardiovascular Health and Physical Activity Level in Terengganu Adults - Qayyum Johari, Muhammad Hanis; Hamdi Dzamakhsari, Muhammad Irfan; Roslim, Nurul Afiedia; Mohd Noor, Siti Maisarah; Rahim , Marhasiyah; Ahmad, Aryati (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2025)
This study aimed to investigate the association between Physical Activity Level (PAL) and body weight status, body composition (body fat percentage, muscle mass, total body water, visceral fat and bone mass) among adults in Terengganu. This study involved 150 participants age ranged from 19–60 years old (72 males and 78 females). PAL was determined using the International Physical Activity Questionnaire (IPAQ), while height, weight and body composition were measured using standard measurement tools. Cardiovascular health and fitness were assessed using blood pressure, heart rate and beep test. Multiple linear regression analysis was employed for data analysis. From the analysis, there was a positive association between PAL and body fat percentage independent of other factors (p=0.003), however, there was no other association with other factors. These findings contribute to our understanding of the influence between body weight, body composition, cardiovascular health and PAL in adults. Although the future study may require a bigger sample size, the finding of this study highlights the importance of physical activity to improve overall health.